Air pollution & migration: Exploiting a natural experiment from the Czech Republic - Stepan Mikula; Mariola Pytliková (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2020)
This paper examines causal effects of air pollution on migration by exploiting a unique natural experiment of desulfurization of power plants in the region of North Bohemia in the Czech Republic after the fall of communism in 1989. The results based on a difference-in-difference estimator show that the estimated effect of reduction in sulfur dioxide (SO2) concentrations on emigration is negative and statistically significant. The effect is sizable: we find that the large reduction in air pollution due to the technology adoption decreased emigration rates from polluted municipalities by approx 24%. The effect is non-linear in the sense that the effect is much larger for municipalities with highest pollution levels prior the desulfurization. Thus, our results suggest that high air pollution loads in the pre-desulfurization period made staying in municipality significantly less desirable, i.e., acted as a strong push factor. All the above results are validated in numerous robustness checks and supported by zero effects from placebo tests. Besides, we explore other historical experimental settings, which allow us to separate out the interplay of possible mechanisms, such as the role of economic benefits, social capital and man-made amenities. All of those channels are otherwise hard to disentangle. Our results based on a triple difference estimator show that the anti-emigration policies had no impact on emigration decisions, whereas we find that the effect of air pollution on emigration tended to be stronger in municipalities with weaker social capital and in municipalities less equipped with man-made amenities. These results suggest that strengthening social capital as well as investing into better facilities in the area of education, health and social care, as well as facilities promoting sport and cultural activities, can partially mitigate the migratory response to air pollution.
Keywords: Q53; J61; O15; 330; air pollution; migration; natural experiment